A systematic new product development methodology for creating affective products - M. Salhieh Ph. D., Sa'Ed (International Journal of Engineering and Technology, 2018)
The success of new product development (NPD) relies on the effective integration of marketing and engineering especially when the development is targeted at creating new products capable of satisfying customer needs generated by feelings, attitudes, and emotions. Such products can be called affective products. This paper introduces a systematic new product development methodology that integrates the processes needed to elicit both tangible/objective and intangible/affective customer needs and translates those needs into product parameters to be used in the development of new products that meet both the customer functional and affective needs. The methodology begins by identifying customer tangible and intangibles needs, then translates those needs into metrics. Next, perceptual mapping is used to determine initial specification and select a new position for the new product. After that, new product concepts are generated and tested. The methodology is illustrated using a case-study application of new pen development.Â Â Â